Hidden Costs in Resident Training: Financial Cohort Analysis of First Assistants in Reduction Mammaplasty. Issue 1 (January 2021) - Malloy, Shannon M.; Sanchez, Karl; Cho, Jonathan; Mulcahy, Sarah E.; Labow, Brian I.
Abstract : Background: Graduate medical education (GME) programs are vital to developing future plastic surgeons. However, their cost-efficiency has yet to be contextualized. This cohort quality improvement (QI) project aimed to measure the indirect costs an institution assumes in training surgical residents, by comparing the differences in operative time and procedural charges between a resident and a physician assistant (PA) first-assisting during adolescent reduction mammaplasty. Methods: From 2013 to 2019, adolescent bilateral reduction mammaplasty procedures first-assisted by either a resident or physician assistant were considered for analysis. Financial data, including all hospital and physician expenditures and operation duration, patient demographics, and outcomes data were retrospectively collected. Results: A total of 49 reduction mammaplasty cases were included for analysis. Residents had an average of 5.9 ± 1.5 years of post-graduate surgical training, whereas the PA had 2 years of surgical experience. Procedures first-assisted by a surgical resident took a mean/median of 34 minutes longer and were 3750 more expensive, respectively, than cases first-assisted by a PA ( P < 0.01, both). Conclusions: Reduction mammaplasty procedures were longer and accrued higher charges when first-assisted by a surgical resident than by a PA. Although Graduate Medical Education programs are necessary to train the next generation of surgeons, they may result in unintended opportunity costs for teaching hospitals. Federal support to academic medical centers aims to cushion the cost of residential training, but is insufficient to compensate for resident inefficiency. Hospitals may consider incorporating PAs into the Graduate Medical Education paradigm to alleviate administrative burden, lower operational charges, and enhance resident training curricula.